ONE DAY ONE MINUTE VLOG TRENDS’ TIKTOK VIDEO PRODUCTION: ENHANCING STUDENTS’ SPEAKING MOTIVATION - Soraya Aisyah; Bambang Yudi Cahyono (IJEE (Indonesian Journal of English Education), 2026)
Social media has been widely utilized by students as a digital tool for learning English, specifically in a context where they might engage as active viewers and content creators rather than formal learners. This study aims to examine the motivational factors driving students’ English-speaking practices through the experiences of “One Day One Minute Vlog” (ODOMV) on the TikTok application. It employed a qualitative method using a narrative inquiry to explore video creators’ motivation in participating in the ODOMV trends. It involved six TikTok users who were purposively selected TikTok users who had actively experienced ODOMV as the current trend of TikTok video production. The personal insights into this trend were gathered by a narrative story framework for the data collection.  The data were collected after the participants completed the ODOMV video trends. The data were analyzed by referring to the basic motivational model theory, which explored the students’ emotions and experiences during the ODOMV journey. The data were analyzed through the process of coding, category development, and theme generation grounded in five emotional themes. The results of this study showed that students were motivated to join the ODOMV video trend based on their confidence, experience, satisfaction, social and cultural motivations, as well as personally and practically motivated reasons. This implies that this video trend creation has motivated the creators to foster their speaking performance. Thus, this study contributes to the development of speaking skills in terms of speaking motivation that serves as an authentic self-directed speaking practice medium, which provides practical implications for English teachers to integrate digital content creation tasks as an English-speaking instruction for out-of-classroom learning activities, as well as supporting the academic achievement from the development of speaking performance through the ODOMV trends.